Correction: Stabilization of negative capacitance in ferroelectric capacitors with and without a metal interlayer. Issue 22 (2nd June 2020) - Rollo, T.; Blanchini, F.; Giordano, G.; Specogna, R.; Esseni, D.
Abstract : Correction for 'Stabilization of negative capacitance in ferroelectric capacitors with and without a metal interlayer' by T. Rollo, et al., Nanoscale, 2020, 12, 6121–6129, DOI: ; 10.1039/C9NR09470A .